Relationship between social perception and mathematical thinking among Malaysian students in higher education - Ali, Rommel Mahmoud (SEAAIR,S. E. Asian Association for Institutional Res., 2015)
This study aimed to investigate the relationship between mathematical thinking and social perception of mathematics among Malaysian students in higher education. The study sample consisted of (150) male and female students from the first year students at Universiti Teknologi Malaysia (UTM). Two instruments were developed which are mathematical thinking skills test MTT, and social perception of mathematics questionnaire SPMQ. The first instrument consisted of 24 questions and the second one consisted of 36 items. The results showed that there were statistically significant differences between the mean averages of students’ scores on the dimensions of social perception of mathematics. In addition, there was a positive relationship between the difficulty of mathematics and its anxiety, and mathematical thinking.